Antimicrobial and anti‐biofilm activities of Bi subnitrate and BiNPs produced by Delftia sp. SFG against clinical isolates of Staphylococcus aureus, Pseudomonas aeruginosa, and Proteus mirabilis. Issue 4 (25th February 2019) - Shakibaie, Mojtaba; Hajighasemi, Elnaz; Adeli‐Sardou, Mahboubeh; Doostmohammadi, Mohsen; Forootanfar, Hamid
Abstract : In the present study Delftia sp. Shakibaie, Forootanfar, and Ghazanfari (SFG), was applied for preparation of biogenic Bi nanoparticles (BiNPs) and antibacterial and anti‐biofilm activities of the purified BiNPs were investigated by microdilution and disc diffusion methods. Transmission electron micrographs showed that the produced nanostructures were spherical with a size range of 40–120 nm. The measured minimum inhibitory concentration of both the Bi subnitrate and BiNPs against three biofilms producing bacterial pathogens of Staphylococcus aureus, Pseudomonas aeruginosa, and Proteus mirabilis were found to be above 1280 µg/ml. Addition of BiNPs (1000 µg/disc) to antibiotic discs containing tobramycin, nalidixic acid, ceftriaxone, bacitracin, cefalexin, amoxicillin, and cefixime significantly increased the antibacterial effects against methicillin‐resistant S. aureus (MRSA) in comparison with Bi subnitrate ( p  < 0.05). Furthermore, the biogenic BiNPs decreased the biofilm formation of S. aureus, P. aeruginosa, and P. mirabilis to 55, 85, and 15%, respectively. In comparison to Bi subnitrate, BiNPs indicated significant anti‐biofilm activity against P. aeruginosa ( p  < 0.05) while the anti‐biofilm activity of BiNPs against S. aureus and P. mirabilis was similar to that of Bi subnitrate. To sum up, the attained results showed that combination of biogenic BiNPs with commonly used antibiotics relatively enhanced their antibacterial effects against MRSA.